Penerapan Sanksi Admnistrasi Terhadap Bangunan Liar di Ruang Terbuka Hijau Kawasan Perumahan di Kota Payakumbuh - Putra, Benny Eka; Haskar, Edi; Arman, Zuhdi (eScience Humanity Journal, 2024)
Green Open Space (RTH) is a part of the city that has no buildings or as few building elements as possible, consisting of natural elements and built elements that function to improve environmental quality. According to the Regulation of the Ministry of Public Works Number 5 of 2008 concerning Guidelines for the Provision of Green Open Space in Urban Areas, each city is required to provide a minimum of 30% of the total city area. There are two types of green spaces, namely public and private green spaces. The research focuses on private RTH where there are often violations committed by developers of residential areas by erecting illegal buildings in the form of housing units categorized as illegal buildings. Illegal buildings are buildings that do not meet the land use and suitability of buildings built in a location. Violations of local regulations related to illegal buildings in RTH still occur in Payakumbuh City. The purpose of this research is to find out how the application of administrative sanctions against violations that occur and analyze the obstacles in the application of these regulations. This research is descriptive using an empirical juridical approach. The results showed that the application of administrative sanctions against violations of local regulations related to illegal buildings in RTH in Payakumbuh City was at a low level. This is caused by several factors so that more commitment is needed from Payakumbuh City stakeholders to the application of administrative sanctions against violators of local regulations related to illegal buildings in RTH in Payakumbuh City.